Facile preparation of magnetic chitosan modified with thiosemicarbazide for adsorption of copper ions from aqueous solution. Issue 9 (3rd November 2016) - Cui, Jing‐Jing; Niu, Cheng‐Gang; Wang, Xiao‐Yu; Zeng, Guang‐Ming
ABSTRACT: In this study, magnetic chitosan modified with thiosemicarbazide (TSC‐Fe3 O4 /CTS) was facilely synthesized with glutaraldehyde as the crosslinker, and its application for removal of Cu(II) ions was investigated. The as‐prepared TSC‐Fe3 O4 /CTS was characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray powder diffraction (XRD), and scanning electron microscopy (SEM). The results showed that TSC‐Fe3 O4 /CTS has high adsorption capacity and selectivity towards Cu(II) ions. Adsorption experiments were carried out with different parameters such as pH, solution temperature, contact time and initial concentration of Cu(II) ions. The adsorption process was better described by the pseudo‐second‐order model. The sorption equilibrium data was fitted well with the Langmuir isotherm model and the maximum adsorption capacity toward Cu(II) ions was 256.62 mg/g. The thermodynamic parameters indicated that the adsorption process of Cu(II) ions was exothermic spontaneous reaction. Moreover, this adsorbent showed excellent reusability and the adsorption property remained stable after five cycles. This adsorbent is believed to be one of the promising and favorable adsorbent for the removal of Cu(II) ions from aqueous solution. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44528. Abstract :